Caregiver’s perception about learning for home care (Acta Scientiarum. Health Sciences, 2017)
The objective was to know the perception of the caregiver about the learning needs of care to be performed at home. This is an exploratory descriptive research, with a qualitative approach. Data collection occurred through a semi-structured interview, from August to October 2014, with six caregivers of patients hospitalized in a medium-sized hospital in the municipality of Santa Maria, Rio Grande do Sul State. The data were analyzed by the content analysis method, identifying two categories: The caregiver's perception about the learning needs; The attendance of the caregiver's learning needs. The study showed that the learning based on empirical, instinctive and observational methodologies, without the participation of the nurse in the process. There is need to improve this learning. The participation of the nurse as an educator in the planning, organization and development of the educational action stands out, since he/she is part of the care; however, the caregivers did not visualize this professional.